ANALYSIS OF FINANCIAL PERFORMANCE AT REGIONAL GENERAL HOSPITAL (RSUD) MALINAU DISTRICT PERIOD 2017-2019 - Rita Melkiana Marbun (SEAN Institute, 2023)
Monetary Ratio Analysis Performance of Common Hospital of Malinau.. Majors Accountancy, target of in this research is to know increase trend / degradation of monetary ratio of RSU Malinau. Method data collecting by conducting survey and calculation of data with ratio analysis analysis which consist of: ratio of likuiditas, solvency ratio and rentability ratio. Result of this research indicate that till year 2019 RSU Malinau ratio current equal to 5,23, its meaning each;every fluent debt equal to Rp. 1,- can be guaranteed with fluent asset equal to 5,23. That way also Debt Assets Ratio to representing the part of solvency ratio namely equal to 0,0182, its meaning each; every totalizeing asset equal to Rp. 1,82,- can be financed by debt equal to Rp. 1,- Percentage 1,82% is good enaugh because smaller this. In the year 2019 value of ROA representing the part of tired rentability ratio value 0.75, its meaning of ability of capital to asset of RSU Malinau to yield advantage of neto is equal to 75%. Each;Every totalizeing asset equal to Rp. 1,- yielding surplus equal to 0,75.Conclusion in this research is ratio analysis of likuiditas RSUD Malinau can be concluded that during year period 2017-2019 happened increase to third ratio ratio that is Currant Ratio, Quick Ratio and of Cash Ratio. This Matter is caused by ever greater fluent asset value and followed by fluent debt value which smaller. While solvebility analysis of RSUD Malinau sultra during year period 2017-2019.